Beyond the code : protection of non-textual features of software - Shemtov, Noam (Oxford University Press, 2017)
Although the law of infringement is relatively straightforward on the copying of literal and textual elements of software, it is the copying of non-literal and functional elements that poses complex and topical questions in the context of intellectual property (IP) protection. This work discusses software as a multi-layered functional product, setting the scene for other legal discussions by highlighting software's unique characteristics. It examines models for the provision of software, addressing licensing patterns and overall enforceability, as well as the statutory and judicial tools for regulating the use of such licences.